2021
DOI: 10.38212/2224-6614.3375
|View full text |Cite
|
Sign up to set email alerts
|

Anti-lymphangiogenic diterpenes from the bark of Calocedrus macrolepis var. formosana

Abstract: Eight new diterpenes, 6α,7β-dihydroxyferruginol (1), 6α,7α-dihydroxyferruginol (2), 6α-hydroxyhinokiol (3), 4α-hydroxy-7-oxo-18-norabieta-8,11,13-trien-4α-ol (4a), 15,16-dehydrosugiol (5), 7-methoxy-6,7-secoabieta-8,11,13-triene-6,12-diol (6), 7α-acetoxyabieta-8,12-diene-11,14-dione (7), 7α-butyloxyethyloxyabieta-8,12-diene-11,14-dione (8), along with four known compounds, 6,7-dehydroferruginol (9), 12-hydroxy-6,7-secoabieta-8,11,13-triene-6,7-dial (10), 7α-11-dihydroxy-12-methoxy-8,11,13-abietatriene (11), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…The protocols for cell culture of human endothelial progenitor cells (EPCs) have been described in detail previously [ 11 ]. The anti-angiogenic activities of selected compounds were evaluated by cell growth assay according to our previous method [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The protocols for cell culture of human endothelial progenitor cells (EPCs) have been described in detail previously [ 11 ]. The anti-angiogenic activities of selected compounds were evaluated by cell growth assay according to our previous method [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…formosana have demonstrated that the leaf, bark, heartwood, and seed essential oils exhibit various beneficial properties. [3][4][5][6][7][8][9][10] These include antioxidant effects, antifungal properties, antibacterial activity, antitermitic properties, mosquito-repellent properties, anti-inflammatory effects, inhibition of lymphangiogenesis, and potential anticancer activity. Based on the available information, there have been no studies conducted to examine the chemical composition or biological activity of the essential oils derived from the twigs of C macrolepis var.…”
Section: Introductionmentioning
confidence: 99%
“…Terpenoids are renowned for their cytotoxic effects on various types of tumors. Interestingly, in the previous investigation, it was discovered that diterpenes possess anti-lymphangiogenic properties, which is a new concept in targeting tumor cell metastasis [37][38][39]. To further explore the relationship between terpenoids and their anti-lymphangiogenic activity, as well as to expand the pharmacological profile of terpenoids, we evaluated the anti-lymphangiogenic activity of the isolated compounds in our study.…”
Section: Introductionmentioning
confidence: 99%